2017
DOI: 10.1097/01.aoa.0000511993.68398.fa
|View full text |Cite
|
Sign up to set email alerts
|

Use of Maternal Early Warning Trigger Tool Reduces Maternal Morbidity

Abstract: (Am J Obstet Gynecol. 2016;214:527.e1–527.e6) Over the past 20 years, maternal mortality has increased unabated in the United States along with a simultaneous increase in severe maternal morbidity. Many national and state organizations have provided recommendations regarding the use of maternal early warning tools to solve this problem. However, there are limited data that support the use of these types of clinical assessment tools to reduce maternal morbidity. The objective of this study were to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 0 publications
1
30
3
1
Order By: Relevance
“…There was no change in the proportion of obstetric complications, ICU admission and length of hospital stay following EWS implementation. Obstetric EWS have been previously shown to prevent progressive obstetric morbidity (14,(24)(25)(26). In contrast to our ndings also, Shields and colleagues, in a large multicentre quasi-experimental trial, reported a signi cant reduction in severe and composite maternal morbidity (p < 0.01) as de ned by the Centre for Disease Control (CDC), but not mortality, in six intervention hospitals following EWS implementation, compared to 19 controls (26).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…There was no change in the proportion of obstetric complications, ICU admission and length of hospital stay following EWS implementation. Obstetric EWS have been previously shown to prevent progressive obstetric morbidity (14,(24)(25)(26). In contrast to our ndings also, Shields and colleagues, in a large multicentre quasi-experimental trial, reported a signi cant reduction in severe and composite maternal morbidity (p < 0.01) as de ned by the Centre for Disease Control (CDC), but not mortality, in six intervention hospitals following EWS implementation, compared to 19 controls (26).…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast to our ndings also, Shields and colleagues, in a large multicentre quasi-experimental trial, reported a signi cant reduction in severe and composite maternal morbidity (p < 0.01) as de ned by the Centre for Disease Control (CDC), but not mortality, in six intervention hospitals following EWS implementation, compared to 19 controls (26). However, they also observed no change in the ICU admission rate in either the intervention or control hospitals (26). We are aware that clinical outcomes would only have been improved if completion of the EWS had led to an escalation of intervention, physician assessment as speci ed by the system, and the institution of appropriate interventions.…”
Section: Discussionmentioning
confidence: 95%
“…25 Maternal early warning system can be implemented during the antenatal to postpartum periods, but it is primarily implemented in hospital settings when a patient is admitted. 26,27 In contrast, the maternal comorbidity index can be used to detect high-risk women, even before pregnancy, for example, during preconception care in primary care settings, as it captures chronic conditions in addition to pregnancy-induced conditions, and can be used to refer these high-risk women to higher level of care. 15 To that end, the objective of this study was to examine the association between maternal comorbidity index and SMM among delivery hospitalizations in Texas.…”
Section: Introductionmentioning
confidence: 99%
“…Highest risk points for this failure were OB triage visits and emergency department visits in the postpartum period. To mitigate these risks, we: Adopted a detailed HDP CPG (based on the 2013 ACOG HDP Task force 16 ) including outpatient assessment/diagnosis, indications for hospitalization and/or delivery, and emergent treatment of elevated blood pressures Adopted a maternal early warning system (MEWS) for postpartum patients 1719 Adopted the Association of Women’s Health, Obstetric, and Neonatal Nurses POST-BIRTH Warning Signs as standard patient education on discharge 20 Provided blood pressure cuffs to all patients with hypertension, together with education on when to present to the hospital based on home monitoring Educated emergency department physicians on postpartum hypertension 21 Mandated critical care transport of HDP patients from outlying hospitals 22 Required completion of online learning module “Hypertensive Disorders of Pregnancy” by all providers and nurses every two years …”
Section: Methodsmentioning
confidence: 99%